A review of myocardial ischaemia/reperfusion injury: Pathophysiology, experimental models, biomarkers, genetics and pharmacological treatment. (6th September 2020) - Gunata, Mehmet; Parlakpinar, Hakan
Abstract : Cardiovascular diseases are known to be the most fatal diseases worldwide. Ischaemia/reperfusion (I/R) injury is at the centre of the pathology of the most common cardiovascular diseases. According to the World Health Organization estimates, ischaemic heart disease is the leading global cause of death, causing more than 9 million deaths in 2016. After cardiovascular events, thrombolysis, percutaneous transluminal coronary angioplasty or coronary bypass surgery are applied as treatment. However, after restoring coronary blood flow, myocardial I/R injury may occur. It is known that this damage occurs due to many pathophysiological mechanisms, especially increasing reactive oxygen types. Besides causing cardiomyocyte death through multiple mechanisms, it may be an important reason for affecting other cell types such as platelets, fibroblasts, endothelial and smooth muscle cells and immune cells. Also, polymorphonuclear leukocytes are associated with myocardial I/R damage during reperfusion. This damage may be insufficient in patients with co‐morbidity, as it is demonstrated that it can be prevented by various endogenous antioxidant systems. In this context, the resulting data suggest that optimal cardioprotection may require a combination of additional or synergistic multi‐target treatments. In this review, we discussed the pathophysiology, experimental models, biomarkers, treatment and its relationship with genetics in myocardial I/R injury. Significance of the study: This review summarized current information on myocardial ischaemia/reperfusion injury (pathophysiology, experimental models, biomarkers, genetics and pharmacological therapy) for researchers and reveals guiding data for researchers, especially in the field of cardiovascular system and pharmacology.